Toward an understanding of mechanisms regulating plant response to biochar application. (2nd January 2019) - Polzella, Antonella; De Zio, Elena; Arena, Simona; Scippa, Gabriella Stefania; Scaloni, Andrea; Montagnoli, Antonio; Chiatante, Donato; Trupiano, Dalila
Abstract: Plant growth and development are affected by several environmental factors, among which soil nutrient availability. Biochar addition to soil is recognized to exert beneficial effects on soil fertility and thus plant growth; furthermore, it is a promising option for climate change mitigation. However, multi-species studies and meta-analyses have indicated considerable variations in biochar responses among plant species. To date, information on the biochar effect on plants, especially at molecular level, is still scarce. Using a multi-target approach with a model plant such as tomato, we demonstrate that biochar has a negligible effect on soil nutrient content and plant growth, even if it misbalances the plant photosynthetic machinery, as well as mechanisms recognizing pathogen-derived molecules. Ethylene could be one of the signal-molecule driving the alteration of tomato-pathogen recognition signaling by inactivation of vesicle trafficking. All these modifications could be at the basis of the increased susceptibility of biochar-treated plants to pathogen attack. Further organ-specific and tissue-specific multi-level studies, from high-resolution internal processes towards high-throughput external phenotyping, coupled with powerful biostatistic and informatic analysis, will help to decipher, in a network-type fashion, all the factors and signaling mechanisms related to the complex interaction between different plant, soil and biochar types.